Power relations in the novel My Name is Alam by Leila S. Chudori - Apriyani, Tristanti; Rosly, Nurul Jamillah Bt. (NOTION: Journal of Linguistics, Literature, and Culture, 2024)
Exploring discursive formations in literary works allows researchers to analyze how language and discourse shape meaning, power dynamics, and cultural ideologies within a specific literary context. Understanding the discursive formations in literary works is crucial for comprehending the historical and social context in which these works were produced. This research aims to describe the forms and representations of power relations in the novel My Name is Alam by Leila S. Chudori. This is qualitative descriptive research where the data is interpreted using the genealogical and archaeological analysis methods promoted by Foucault. This method aims to uncover and understand hidden power dynamics in various aspects of human life. The research results prove that the author's statements were spread across various formations and became material for discussion. Two forms of power relations are being discussed; the first is the New Order government's practice of authoritarian power in its various policies, which limits human rights. Second, there is resistance from marginalized groups, namely political prisoners and their families. This form of resistance is an effort by marginalized groups to fight for equality and justice. The New Order government in Indonesia constructed a discourse to create a simulated space to legitimize its power within national memory politics. This simulated world is a blend of reality and fantasy constantly reproduced. As a result, the actual reality becomes obscured, and the symbols created are perceived as reality.